PENGARUH PENERAPAN AKUNTANSI PEMERINTAHAN BERBASIS AKRUAL, DAN PENGENDALIAN INTERN TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH PADA DINAS KOMUNIKASI INFORMATIKA DAN STATISTIK PROVINSI LAMPUNG - Sekar Sari, Meita; Silvia, Dewi; Putri, Aprilia Eka (Jurnal Ilmiah Ekonomi Dan Bisnis, 2023)
The aim of this research is to find out how much influence the implementation of Accrual-Based Government Accounting Standards and Internal Control has on the Quality of Government Financial Reports. This research uses a quantitative descriptive approach where the data processing is carried out statistically. The number of samples taken was 104 respondents using the Saturated Sampling method, a group from Non Probability Sampling, which was carried out by census where the population was used as a sample registered with the Lampung Province Communications, Information and Statistics Service. The data source in this research is primary data obtained using a questionnaire which was then processed using multiple linear analysis tests using SPSS version 21. The results of this research show that the implementation of Accrual-Based Government Accounting Standards and Internal Control simultaneously and partially has a positive and significant effect on Quality of Government Financial Reports. Keywords: Accrual Based Accounting, Internal Control, Quality of Financial Reports